Model Pembelajaran Matematika SMP untuk mengatasi rendahnya kompetensi dasar siswa SMP kota Bengkulu: basic competence, mathematics learning - Effie Efrida Muchlis (Buana Pendidikan, 2015)
. The purpose of the study are: 1) find a description of the factors causing low mastery of basic math competency Junior high school students in the Bengkulu City. 2) Generate a valid mathematical model of learning, practical and effective way to improve the competence of Junior high school (SMP) students in the Bengkulu City. To achieve this goal done two phases the first phase is a quantitative and qualitative research (mixed) by applying documentation studies, focus group discussions, in-depth interview and classroom observation. The second phase is the development by implementing Research Design Development (Plomp& Nieveen , 2007) to generate alternatives valid mathematical model of learning, practical and effective to improve the competence of learners in mathematics learning in junior high schools in the Bengkulu City. Results of this study were 1) The factors causing low competence junior high school students in learning mathematics in the Bengkulu City are as follows: Education Management Systems and Learning Mathematics: mathematics learning management tend to be rigid and mechanistic; Teacher: Teachers of Mathematics Having Lesson Planning Document, but in the implementation of learning is not in accordance with the plan that is prepared; Teachers deliver learning materials more emphasis to achieve the target of the curriculum, not to achieve competence, by reason of the allocation of time, and catch-material for students dealing with the national assessment (UN); Media Learning Mathematics: The utilization of instructional media, facilities and infrastructure to support the learning of mathematics has not been used optimally; Model Learning / Learning Strategies: Teachers in the communication of such materials using learning shekel: Presentation of lecture material with the form of definition, and the formula, then the teacher gives examples of problems, followed by exercises and the provision of home tasks, and so on is done repeatedly. 2) Mathematics Learning Model SMP (MPM-SMP) Prototype Devices Learning as one of the supporting system of the learning model is valid, and practical, yet effective for improving the competence of junior high school students in the city of Bengkulu is still in the process of tabulation and analysis of data.